Relations between corporate economic performance, environmental disclosure and greenhouse gas emissions: New insights. (13th February 2018) - Hassan, Omaima A.G.; Romilly, Peter
Abstract: This study examines the associations and causations between corporate economic performance, environmental disclosure and greenhouse gas emissions, utilizing a large, longitudinal, multicountry dataset disaggregated between developed and developing countries. The methodology uses a simultaneous equation model with system estimation to deal with endogeneity between the variables, and Granger causality tests to indicate their direction of causation. A robust result is that lower emissions are strongly associated with better economic performance. After pretesting for stationarity, we find evidence of a one‐way causation from emissions and environmental disclosure to economic performance, but no evidence of reverse causation. We also find strong evidence of a one‐way causation from emissions to disclosure, but no evidence of reverse causation. The overarching policy implication is that environmental performance, as measured by greenhouse gas emissions, plays a crucial role in the formulation of business strategy at the firm level and government environmental policy at national and international levels.